Efficacy and safety of diphenylcyclopropenone among Chinese patients with steroid resistant and extensive alopecia areata. (12th October 2012) - Luk, N.M.; Chiu, L.S.; Lee, K.C.; Chau, C.T.S.; Lee, V.W.Y.; Chang, M.; Lam, Y.K.; Lee, H.C.
Abstract Background Topical immunotherapy has recently been found useful in the treatment of chronic and extensive Alopecia Areata (AA). Objective To evaluate the efficacy and safety of diphenylcyclopropenone (DPCP) use among Chinese patients with steroid resistant and extensive AA in our institute. Methods The medical records of 31 Chinese patients treated with DPCP were analysed retrospectively. The efficacy, adverse effects, and relapse rate of DPCP treatment were reviewed. Results Thirty‐one (16 male, 15 female) Chinese patients with extensive, steroid resistant Alopecia Areata and a mean age of 28.9 years (SE 10.4) were treated. The mean age of onset was 17.8 years (SE 8.8) with an average disease duration of 11.2 years (SE 7.7). Ten patients had a history of atopy and 4 had a history of thyroid disease. Nail changes were found in 14 patients and a family history of AA was found in 2 patients. Thirteen patients (41.9%) had experienced total hair loss. Two patients abandoned the treatment due to severe side effects. Of the remaining 29 patients, 4 (13.8%), 7 (24.1%), 5 (17.2%), and 13 (44.8%) achieved >90% complete response, >50–90% partial response, >10–50% minimal response, and <10% no response hair regrowth, respectively. Adverse effects included pruritus, erythema, vesiculation, scaling, cervical lymphadenopathy, dyspigmentation and urticarial reactions. Relapse occurred (>25% hair loss) in 69.23% of patients after 18 months of follow up. Conclusions DPCP is an effective and tolerable treatment for Chinese patients with extensive, steroid resistant AA.